Peningkatkan Pembelajaran Passing pada Materi Sepak Bola Melalui Metode Learning Together - Ade Brilliant Pratama; Faridha Nurhayati; Indra Bagus Lesmana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The passing ability of class 5 B students at SDN Lidah Wetan II/462 can be improved by learning football passing material using the learning together method in PJOK learning, based on the findings of two cycles of classroom action research. The increase in football passing ability from pre-cycle, cycle I to cycle II shows this. Football passing has an average value of 62.20 in the pre-cycle. The average score increased to 67.62 in the first cycle of student assessment results, and to 77.24 in the second cycle, a quite good change. It can be seen that this increase illustrates that students' soccer passing abilities have experienced quite good changes in each process.